Magical Healer and the Son of God. Jesus’ Healings as a Magic Ritual and the Phenomenon of De-Ritualization in the Editorial Transmission of the Gospels - Krahn, Annika (ARYS. Antigüedad: Religiones y Sociedades, 2020)
While the depiction of Jesus as a charismatic healer is widely known, his use of magical rituals in connection with those healings is a neglected topic in New Testament exegesis. This may be due to the fact, that in the Christian context magic was soon associated with dubious ritual practices trying to manipulate God’s will. The sources, however, offer no objective criteria on the basis of which one could reliably distinguish between charismatic and magical rituals. Instead, the perception of an act as (evil or illegitimate) magic vs. a (good and desired) charismatic healing depended entirely on the perspective: While magical rituals performed by Jesus are characterized as charismatic acts because they derived their power from the right authority, similar rituals executed by “others” are devaluated as illegitimate forms of magic. Consequently, one can observe a process of de-ritualization within the synoptic tradition which served to free Jesus from the obscure attribution of being a magician (outsider’s point of view) and to establish him as the Messiah and the only-born Son of God (insider’s point of view).